PROBLEMS OF DETERMINING THE UNDERWATER CULTURAL HERITAGE FOR QUALIFICATION UNDER ARTICLE 298 OF THE CRIMINAL CODE OF UKRAINE - Гуляков, Константин; Сотула, Александр (SWorldJournal, 2020)
The article is devoted to the study of domestic legislation on the protection of objects of underwater cultural heritage. The article analyzes the problems of the criminal law definition of objects of underwater cultural heritage, taking into account th